INTERACTIVE TECHNOLOGIES IN TEACHING HISTORY - Nazarov Sardorbek (Western European Studies, 2024)
This article is based on modern interactive methods of teaching subject history and general education. The author analyzes the effectiveness of using interactive methods.
Keywords: interactive method; subject history; technology